Revitalization of Marine Culture Through Maritime Based Development Policy in Indonesia - Ummil Khalish; Febriansyah Febriansyah (Journal of Maritime Policy Science, 2025)
Indonesia, as the world’s largest archipelagic state, possesses a rich maritime heritage shaped by centuries of seafaring and coastal livelihoods. However, national development has long prioritized land-based sectors, marginalizing maritime culture within policy frameworks. This study aims to analyze how maritime-based development policies can serve as instruments for revitalizing maritime culture and to identify the challenges and opportunities for their implementation. Employing a descriptive qualitative approach, the research draws upon Edward III’s policy implementation theory to examine policy communication, resource adequacy, bureaucratic structure, and implementers’ disposition as determinants of success. Data were obtained through documentation studies, secondary data from government institutions, and semi-structured interviews with policymakers, cultural actors, and coastal community leaders. The findings reveal that while comprehensive legal instruments such as Law No. 5 of 2017 on Cultural Advancement and Presidential Regulation No. 16 of 2017 on Indonesian Marine Policy exist, implementation remains weak due to fragmented inter-agency coordination, limited resources, and insufficient political commitment. Some local innovations, such as culture-based marine schools and regional maritime heritage mapping, demonstrate potential best practices. The study concludes that revitalizing maritime culture requires integrating socio-cultural values into policy planning, strengthening institutional capacity, and involving coastal communities as key actors. Such efforts are essential to transform maritime culture from a symbolic narrative into a substantive foundation for sustainable and inclusive national development.